Improving Students English Vocabulary by Using Tic Tact Toe Game at The second Year of SMP Negeri 7 Satap Maiwa Kabupaten Enrekang - Hasan Hasan (Edumaspul: Jurnal Pendidikan, 2018)
This research was intended to explain the students English vocabulary by using Tic Tact Toe game at the second year of SMP Negeri 7 Satap Maiwa in the 2016/2017 academic year. In this research used quasy experimental class. It had conducted in two groups namely experimental group and control group. The population in this research were students in class VIII involved 30 students. The researcher took real data from the class to know the students English vocabulary . the instruments of this research were pre-test and post-test with multiple choice. From these findings, there was significance improvement of the students English vocabulary by using Tic Tact Toe game.